E-Learning: Metode Pembelajaran Masa Depan yang Efektif dan Efisien - Irfan Haryanto; Amelia Setiawan; Hamfri Djajadikerta (Syntax Corporation, 2023)
Currently E-learning emerges as a new paradigm in the field of modern education and many studies have shown empirical evidence that it can effectively improve employee competency and performance. This study aims to identify and analyze the latest studies related to the implementation of E-learning from 2018 to 2023 to explore and see how far the phenomenon of the development of the E-learning method is when viewed from three timeframes, namely during the period before the Covid-19 pandemic, namely 2018 -2019, then during the Covid-19 pandemic, namely 2020-2022 and during the period after the Covid-19 pandemic in 2023 using the Systematic Literature Review (SLR) method with the help of Publish or Perish, Mendeley, Zotero, and Microsoft Excel tools. The results showed that of the 61 articles selected based on article searches in 2018-2019 (before the covid19 pandemic), 2020-2022 (during the covid19 pandemic), in April 2023 (after the covid19 pandemic), so that 9 articles were obtained that met quality assessment. Utilization of E-learning as a means of training and learning can improve employee competency. With the implementation of E-learning, employees can implement the skills or abilities that have been acquired which make employees more capable in responding to job demands. The e-learning process as a medium for employee training and development is able to provide a comprehensive learning experience for employees. E-learning is used as an alternative or a solution to face-to-face training to increase employee competence.